Cerebral endothelial cell-derived small extracellular vesicles enhance neurovascular function and neurological recovery in rat acute ischemic stroke models of mechanical thrombectomy and embolic stroke treatment with tPA. Issue 8 (August 2021) - Li, Chao; Wang, Chunyang; Zhang, Yi; Alsrouji, Owais K; Chebl, Alex B; Ding, Guangliang; Jiang, Quan; Mayer, Stephan A; Lu, Mei; Kole, Max K; Marin, Horia L; Zhang, Li; et al.
Treatment of patients with cerebral large vessel occlusion with thrombectomy and tissue plasminogen activator (tPA) leads to incomplete reperfusion. Using rat models of embolic and transient middle cerebral artery occlusion (eMCAO and tMCAO), we investigated the effect on stroke outcomes of small extracellular vesicles (sEVs) derived from rat cerebral endothelial cells (CEC-sEVs) in combination with tPA (CEC-sEVs/tPA) as a treatment of eMCAO and tMCAO in rat. The effect of sEVs derived from clots acquired from patients who had undergone mechanical thrombectomy on healthy human CEC permeability was also evaluated. CEC-sEVs/tPA administered 4 h after eMCAO reduced infarct volume by ∼36%, increased recanalization of the occluded MCA, enhanced cerebral blood flow (CBF), and reduced blood-brain barrier (BBB) leakage. Treatment with CEC-sEVs given upon reperfusion after 2 h tMCAO significantly reduced infarct volume by ∼43%, and neurological outcomes were improved in both CEC-sEVs treated models. CEC-sEVs/tPA reduced a network of microRNAs (miRs) and proteins that mediate thrombosis, coagulation, and inflammation. Patient-clot derived sEVs increased CEC permeability, which was reduced by CEC-sEVs. CEC-sEV mediated suppression of a network of pro-thrombotic, -coagulant, and -inflammatory miRs and proteins likely contribute to therapeutic effects. Thus, CEC-sEVs have a therapeutic effect on acute ischemic stroke by reducing neurovascular damage.